Municipal Courts and Environmental Justice in South African Local Government - Molaiwa, Andrew (Potchefstroom Electronic Law Journal, 2021)
Environmental injustice is part and parcel of the fundamentals of international and domestic environmental law. In South Africa, section 2(4)(c) of the National Environmental Management Act 107 of 1998 (NEMA) establishes environmental justice (EJ) as part of the environmental management principles to direct decision-making. This is particularly relevant because of the country’s legacy of continuing environmental injustices and inequalities, especially concerning natural-resource dependent services and benefits. The Constitution of the Republic of South Africa, 1996 further establishes a developmental local government (DLG) of which the objects are to ensure a safe and healthy environment, sustainable delivery of services, promotion of social and economic development as well as public participation in decision-making. These objects are complemented by section 24 environmental right in the Bill of Rights. Municipal service delivery of water and sanitation, electricity, land matters and municipal health, should supplement, not compromise the state of local communities’ environment and access should be equal. The absence of the latter may result in the form of environmental injustice as has been described by authors such as Bullard, McDonald and Schlosberg. In the event of service delivery-related environmental injustices, it is to be expected that communities must have remedial options available. One of which may be accessible to the judicial system. Therefore, this paper focuses on and explains the role that Municipal Courts specifically may play in fortifying the relationship between municipal service delivery and improved grass-root level environmental justice in South Africa. The underlying question is whether such courts can be agents of (environmental) change where local communities are exposed to environmental harm as a consequence of the failure of municipal services or the environmentally harmful actions of other community members or local industries.